Education for Digital and Remote Education: report of the training experience of teachers of IFRS - Campus Porto Alegre - Aline Grunewald Nichele; Gabriela Fernanda Cé Luft; Karen Selbach Borges; Márcia Bündchen (Universidade Federal do Oeste da Bahia, 2021)
This experience report addresses the teacher training action developed at Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFRS) - Campus Porto Alegre, between June and August 2020. Eleven workshops about digital technologies in education and active methodologies were conducted through online platforms, reaching 75% of Porto Alegre Campus teachers. The context that motivated this teacher training experience and it's development stages will be presented in this paper. As a result, we highlight the success of the reported action as a way to provide teachers new competencies to adopt digital technologies for remote education amid the pandemic.Such action also serves as a stimulus for digital education activities to be adopted in other educational institutions.